The Role of Innovation in the Success of Modern Startupreneurs - Alwiyah Alwiyah; Naomi Lyraa (Startupreneur Business Digital (SABDA Journal), 2024)
The study examines Innovation Capability, Team Creativity, External Environ- ment, and Start-up Performance as key research factors, the study attempts to investigate the impact of innovation in the success of contemporary businesses. Innovation Capability, Team Creativity, External Environment, and Start-up Per- formance are the research factors that were examined. (Start-up Function). Through surveys of start-ups in a variety of industry sectors, the data was gath- ered. The analysis’s findings demonstrate that a start-up’s performance is sig- nificantly impacted by its capacity for innovation. It has also been discovered that team creativity is crucial for enhancing innovation and startup performance. The creativity driving innovation is significantly enhanced by frequent brain- storming sessions and diverse team backgrounds, the diversity of backgrounds within the team, and the degree of team collaboration. Furthermore, govern- mental regulations, technological accessibility, and cooperative networks with academic institutions are examples of the external environment that fosters cre- ativity and improves start-up performance.The study’s conclusions highlight the importance of innovation in the success of contemporary startupreneurs. Sup- porting innovation and enhancing business performance also heavily depends on the inventiveness of the team and a favorable external environment. Therefore, strategic measures to success in contemporary entrepreneurship include devel- oping an ecosystem that fosters invention, managing team dynamics skillfully, and establishing an organizational culture that values creativity